Are Mediterranean Marine Protected Areas sheltered from plastic pollution?. (March 2019) - Liubartseva, S.; Coppini, G.; Lecci, R.
Abstract: Comparisons of six selected Mediterranean MPAs were conducted to find similarities and site-specific differences in coastline fluxes and sources of plastic marine litter. Output from the recently developed 2D Lagrangian model for the Mediterranean was post-processed to study (1) the National Park of ses Salines d'Eivissa i Formentera, (2) Nature Reserve of Bouches de Bonifacio, (3) North-East Malta MPA, (4) Specially Protected Area of Porto Cesareo, (5) Community Importance Site of Torre Guaceto, and (6) Ethniko Thalassio Parko Alonnisou Voreion Sporadon. Model coastline fluxes of plastic ranged from 0.4 to3.6 kg (km day) −1, which is relatively low compared to the average flux of 6.2 ± 0.8 kg (km day) −1 calculated over the Mediterranean 2013–2017. Shipping was identified as a major source of plastic litter in all MPAs studied, contributing 55%–88% of total plastic. Site-specific rankings of the top 5 land-based plastic sources revealed that sea surface kinematics control plastic drift. Highlights: 6 selected MPAs were studied by means of previously developed 2D Lagrangian model. Lagrangian inverse problem helps rank the sources of plastic. Synergy of anthropogenic drivers and hydrodynamic transport is clearly visible. Shipping plays a key role in plastic pollution for all studied MPAs. Further quantification of plastic sources is a matter of great importance.